LIGHT POLLUTION IN URBAN AREAS & BEST PRACTICE - N. Supriya; Kumar, Shashikant (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The surge in artificial light usage, following the invention of the first light bulb, has been exponential, resulting in the pervasive issue of light pollution. This phenomenon is primarily attributed to economic development, population growth, and urban sprawl, posing an escalated risk of health issues. The primary goal of this study is to pinpoint the adverse effects of light pollution, recognize the intrinsic value of dark skies as a precious resource, and comprehend the benefits associated with their preservation. The exploration will commence with an examination of the various types and causes of light pollution and their impacts on both animals and human health. Subsequently, attention will shift to elucidating basic standards and methodologies for measuring light pollution, encompassing the tools and techniques involved. The discussion will culminate in an exploration of strategies for planning dark skies, underscoring the crucial role of local authorities in conjunction with best practices, and presenting an overview of the current situation within the study area.